Ethnomathematical Analysis of Wapauwe Kaitetu Old Mosque Building: Between Myth and Science - Sopamena, Patma; Sangkala, Nani Sukartini; Kaliky, Syafrudin; Juhaevah, Fahruh; Rumakabis, Muhammad Sidiq (FKIP Universitas Lampung, 2023)
This study aims to explore public perception of the existence of the Wapauwe Kaitetu mosque which involves mathematical concepts in building construction. Therefore, this research method is qualitative with a descriptive-exploratory approach. This research was carried out in Kaitetu village, Central Maluku with two subjects, namely community leaders and mosque guards who knew the existence of the Wapauwe Kaitetu mosque. The instruments used are interview guidelines and observation sheets. The mathematical objects in the Wapauwe Kaitetu mosque are: quadrilateral (square and trapezium); elliptical; triangle; circle; spaces (cubes, trapezoidal prisms, pyramids and tubes); compass; and deep congruences. Furthermore, myth (using telepathy as a means of communication with other dimensional societies) and science (building construction using good quality wooden frames and close connecting wood distances resulting in mosque buildings becoming sturdy and strong). Furthermore, it is suggested that further researchers can examine the ethnomathematical implementation of the Wapauwe Kaitetu mosque in the mathematics learning process. Keywords: ethnomathematics, mosque construction, Wapauwe Kaitetu mosque, myth and science.DOI: http://dx.doi.org/10.23960/jpmipa/v24i2.pp467-480